(untitled) (Gestão & Regionalidade, 2016)
This paper aimed to study the social development policies of three municipalities of the state of São Paulo: Americana, Cajurú and São Caetano do Sul, from social and economic indicators, combining them with educational outcomes. From the theoretical frameworks, field researches, data collected from IBGE, Seade Foundation and the evaluations of Education Ministry, EducaCenso/Ideb, in 2007, 2009, 2011 and 2013, a conceptual framework could be prepared, whose results reveal that the indices of wealth and development are not directly correlated with the performance of local public education, as well as full time school does not represent better education quality. A management model focused on education quality brought evidence of being a central aspect to the results of education.